2023
DOI: 10.3389/fpsyt.2023.1218340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a mindfulness-based interventions on stress, burnout in nurses: a systematic review and meta-analysis

Qi Wang,
Fang Wang,
Shurong Zhang
et al.

Abstract: BackgroundStress in the healthcare environment causes negative effects in nurses such as burnout, anxiety, and depression. The COVID-19 pandemic has resulted in increased pressure on medical staff globally, highlighting the potential benefits of mindfulness-based interventions in reducing nurses’ stress levels. Despite numerous studies exploring the effect of mindfulness-based training on nurses, the results remain inconclusive.ObjectiveTo systematically evaluate the impact of mindfulness training on nurse’s p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…Most of them focus on a single occupational category and evaluate a single type of program. We confirm the results of some other studies from the literature showing the beneficial effects of mindfulness-based programs on burnout in the health sector: medical students (63,(70)(71)(72), nurses (66,(73)(74)(75)(76)(77), physicians (78)(79)(80), or health professionals as a whole (58,64,81,82). We found only one study which, like ours, was 61).…”
Section: Effects On Burnoutsupporting
confidence: 89%
See 1 more Smart Citation
“…Most of them focus on a single occupational category and evaluate a single type of program. We confirm the results of some other studies from the literature showing the beneficial effects of mindfulness-based programs on burnout in the health sector: medical students (63,(70)(71)(72), nurses (66,(73)(74)(75)(76)(77), physicians (78)(79)(80), or health professionals as a whole (58,64,81,82). We found only one study which, like ours, was 61).…”
Section: Effects On Burnoutsupporting
confidence: 89%
“…Studies carried out with health professionals also showed more empathy, better communication between professionals, better emotional regulation and increase in well-being (57)(58)(59)(60). Additionally, recent meta-analysis showed that mindfulness might have beneficial effects on burnout among health workers, but few RCTs (2)(3)(4)(5)(6) were included in these studies (61)(62)(63)(64)(65)(66).…”
Section: Mindfulnessmentioning
confidence: 99%